ECCO Guidelines on Therapeutics in Ulcerative Colitis: Surgical Treatment. (17th October 2021) - Spinelli, Antonino; Bonovas, Stefanos; Burisch, Johan; Kucharzik, Torsten; Adamina, Michel; Annese, Vito; Bachmann, Oliver; Bettenworth, Dominik; Chaparro, Maria; Czuber-Dochan, Wladyslawa; Eder, Piotr; Ellul, Pierre; et al.
Abstract: This is the second of a series of two articles reporting the European Crohn's and Colitis Organisation [ECCO] evidence-based consensus on the management of adult patients with ulcerative colitis [UC]. The first article is focused on medical management, and the present article addresses medical treatment of acute severe ulcerative colitis [ASUC] and surgical management of medically refractory UC patients, including preoperative optimisation, surgical strategies, and technical issues. The article provides advice for a variety of common clinical and surgical conditions. Together, the articles represent an update of the evidence-based recommendations of the ECCO for UC.